Theoretical reflections on compensation for non-pecuniary damage arising from the violation of the right to a healthy environment - Stanojević, Petra (Glasnik Advokatske komore Vojvodine, 2025)
The Constitution of Serbia guarantees the right to a healthy environment, while the Law on Obligations provides the possibility of non-pecuniary damage compensation due to the violation of personality rights. This paper analyzes whether the right to a healthy environment is considered a personality right, what constitutes its violation, and whether a lawsuit for compensation of non-pecuniary damage due to its violation is the most effective mechanism for protecting the rights of individuals affected by pollution.